Latent tuberculosis infection and active tuberculosis in patients with psoriasis: a study on the incidence of tuberculosis and the prevalence of latent tuberculosis disease in patients with moderate–severe psoriasis in Spain. BIOBADADERM registry. (8th November 2012) - Sánchez‐Moya, A.I.; García‐Doval, I.; Carretero, G.; Sánchez‐Carazo, J.; Ferrandiz, C.; Herrera Ceballos, E.; Alsina, M.; Ferrán, M.; López‐Estebaranz, J.‐L.; Gómez‐García, F.; De la Cueva Dobao, P.; Carrascosa, J.‐M.; et al.
Abstract Introduction The incidence of tuberculosis (TB) or the prevalence of latent tuberculosis infection (LTBI) in psoriasis patients has not been described in the Spanish population. We carried out a study with the objectives: (i) To describe the incidence of TB in patients with psoriasis on systemic treatment in the Spanish population; (ii) To determine the prevalence of LTBI in patients who are candidates for biological treatment; and (iii) To investigate the level of compliance with current recommendations for LTBI and TB screening. Methods Data were obtained from BIOBADADERM (Spanish registry for systemic biological and non‐biological treatments in psoriasis). An analysis was performed of the exposed cohort to determine the prevalence of LTBI and to describe compliance with the screening guidelines. Results A total of 1425 patients were registered in BIOBADADERM. They included 793 (56%) patients exposed to biological treatment and 632 (44%) treated with conventional systemic drug. Overall follow‐up was 3720 person‐years. Of the 793, 20.5% (163) were diagnosed with LTBI before starting biological treatment. The rate of active TB for the exposed cohort was 145 cases × 100 000 patient‐years (95% CI 54–389). No case of TB was found in the control group. Screening for LTBI was performed in 83% of the exposed sample. Conclusion Patients with psoriasis who are exposed to biological treatment appear to be at greater risk for tuberculosis. In Spain, up to 20% of patients with psoriasis who are candidates for biological therapy have LTBI. There continues to be a significant percentage of errors in compliance with clinical guidelines.